1995
DOI: 10.1159/000168799
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function in Gout Patients

Abstract: Patients with gouty arthritis were examined at Veterans General Hospital to evaluate whether their renal function is impaired and to define the factor(s), if any, of renal function deterioration. A total of 152 cases were included in the study, and the patients were divided into two groups. One group (n = 80) exhibited pure gout without any associated medical problems or preexisting renal disorders. The second group (n = 72) included patients with gout and hypertension. The group with pure gout was further str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 16 publications
0
16
0
3
Order By: Relevance
“…50 Apart from the increased risk of developing kidney stones, such effects seem to contribute to a decrease in GFR aggravated by the presence of hypertension. 51 In the early 1960s, Talbott and Terplan, 52 reported that 10-20% of patients with untreated gout developed ESRD. Moreover, renal biopsies in these patients revealed tubulointerstitial fibrosis, arteriosclerosis, and glomerulosclerosis.…”
Section: Gouty Nephropathy and Ckdmentioning
confidence: 99%
“…50 Apart from the increased risk of developing kidney stones, such effects seem to contribute to a decrease in GFR aggravated by the presence of hypertension. 51 In the early 1960s, Talbott and Terplan, 52 reported that 10-20% of patients with untreated gout developed ESRD. Moreover, renal biopsies in these patients revealed tubulointerstitial fibrosis, arteriosclerosis, and glomerulosclerosis.…”
Section: Gouty Nephropathy and Ckdmentioning
confidence: 99%
“…Кроме того, согласно современным представлениям, нарушение функции почек у больных подагрой может быть обусловлено и наличием АГ, гиперлипидемии, сахар-ного диабета (СД) 2-го типа [28][29][30].…”
Section: коморбидные заболевания при подагреunclassified
“…Поражение почек, часто наблюдаемое при подаг-ре, ассоциируется с возрастом, полом и длительно-стью болезни [10,12,13,17,18]. В нашей работе СКФ обратно коррелировала с возрастом больных и была достоверно выше у пациентов молодого возраста по сравнению с пожилыми, что частично можно связать и с естественным влиянием старения на функцио-нальную способность почек.…”
Section: с в я з ь с к ф с и т п о д а г р ы и е г о к о м п о н е н unclassified
“…Таким образом, поражение почек, часто наблюда-емое при подагре, ассоциируется с множеством фак-торов: возрастом и полом больных, длительностью болезни, а также с кардиоваскулярными факторами риска [10,12,13,17,18].…”
unclassified